2001
DOI: 10.1177/153857440103500105
|View full text |Cite
|
Sign up to set email alerts
|

Does a Postimplantation Syndrome Following Endovascular Treatment of Aortic Aneurysms Exist?

Abstract: The postimplantation syndrome (PIS) is a weakly defined condition that has been observed following endovascular treatment of aortic aneurysms; the postulated criteria include significant leukocytosis, fever, and/or coagulation disturbances. Among the factors that are supposed to contribute to this syndrome are contact activation by the stent covering with consecutive endothelial activation. Associated clinical parameters of a PIS were perioperatively monitored in the postoperative phase in a total of 69 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…two groups. Incidence of postimplantation syndrome, defined as the presence in the postoperative period of fever, leukocytosis, or coagulation disturbances, 21 was similar between the two groups. Four reinterventions were performed in the IFU group (2 sutures of arteriotomy for false aneurysm in access site, 1 thrombectomy and 1 femorofemoral crossover prosthetic bypass graft for limb graft thrombosis).…”
Section: Resultsmentioning
confidence: 81%
“…two groups. Incidence of postimplantation syndrome, defined as the presence in the postoperative period of fever, leukocytosis, or coagulation disturbances, 21 was similar between the two groups. Four reinterventions were performed in the IFU group (2 sutures of arteriotomy for false aneurysm in access site, 1 thrombectomy and 1 femorofemoral crossover prosthetic bypass graft for limb graft thrombosis).…”
Section: Resultsmentioning
confidence: 81%
“…2,4 Postoperative pyrexia has been shown to be more common (72%) in endovascular repair than in open repair (38%). 5 Inflammatory markers were not measured in this study as they have been well shown to be elevated after endovascular aneurysm repair. The white cell count (WCC) peaks at 24-72 h, the C-reactive protein (CRP) at 48-72 h and interleukin-6 (IL-6), interleukin-8 (IL-8) and interleukin-1β (IL-1β) also rise.…”
Section: Discussionmentioning
confidence: 97%
“…The white cell count (WCC) peaks at 24-72 h, the C-reactive protein (CRP) at 48-72 h and interleukin-6 (IL-6), interleukin-8 (IL-8) and interleukin-1β (IL-1β) also rise. 3,5,6 The combination of fever, elevated white cell count and CRP with or without a coagulation disturbance is known as the post implantation syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the incidence of PIS ranges from 3 to 94% due to differences in the definition of PIS. 2,8) A study compared EVAR with open surgery, and indicated that fever after open surgery was observed in 38% of the patients, whereas post-EVAR fever was noted in 72%, 9) suggesting that PIS is a phenomenon specific to EVAR. We consider that even EVAR, which is minimally invasive, may reduce appetite or ADL through fever, and that inhibition of postoperative inflammation leads to an improvement in the quality of life (QOL).…”
Section: Discussionmentioning
confidence: 99%